Les enseignants et la diversité ethnoculturelle : entre différenciation et homogénéisation dans les discours et les pratiques pédagogiques - Geneviève Mottet
The aim of this article is to present the ambivalent relationship that teachers have with the ethnocultural diversity of their students. We will see that they mobilise two intertwined and opposing patterns of discourse and practice. On the one hand, professionals seek to promote differentiated instruction and to take into account the diversity of school audiences. On the other hand, they paradoxically develop practices and produce discourses that seek to erase it, with a perspective of homogenisation, seeking to adjust the public to school and societal norms; that is, to induce good behaviour and promote the common culture.